2022
DOI: 10.1371/journal.pone.0275616
|View full text |Cite
|
Sign up to set email alerts
|

How do manufacturing and producer service agglomerations affect urban innovation differently? Empirical evidence from China

Abstract: Despite the growing body of literature on the influence of industrial agglomeration on urban innovation, no consensus has been reached on the mechanism of the spillover effect. This empirical study exploits heterogeneity in spillover effects between manufacturing and producer service agglomerations on urban innovation based on a sample of 262 prefecture-level cities in China. We find some intriguing and new findings: (1) The threshold effect can be identified for the spillover effect of manufacturing agglomera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…First, the robustness test is performed by selecting other indicators as explanatory variables and the independent variable manufacturing industrial agglomeration ( magg ) is replaced with manufacturing employment density ( mden ) which is the ratio of manufacturing employment to the area. Furthermore, based on the empirical evidence of Zhang et al [ 56 ], including the one-period lagged independent and control variables can alleviate the potential endogeneity problem. Thus, the robustness is also tested by adopting the one-period lagged manufacturing industrial agglomeration ( magg t −1 ) instead of manufacturing industrial agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…First, the robustness test is performed by selecting other indicators as explanatory variables and the independent variable manufacturing industrial agglomeration ( magg ) is replaced with manufacturing employment density ( mden ) which is the ratio of manufacturing employment to the area. Furthermore, based on the empirical evidence of Zhang et al [ 56 ], including the one-period lagged independent and control variables can alleviate the potential endogeneity problem. Thus, the robustness is also tested by adopting the one-period lagged manufacturing industrial agglomeration ( magg t −1 ) instead of manufacturing industrial agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, it may be affected by various factors such as economic development level, regional layout, and foreign investment. For example, Zhang et al discovered that different levels of regional development lead to the gradual weakening of the spillover effect of industrial agglomeration due to the siphoning effect of surrounding cities, which ultimately manifests as a diminishing regional innovation effect [31], while Kekezi and Klaesson pointed out that spillover effects of knowledge-intensive industry agglomeration diminish with increasing geographical distance and may impose adverse impacts on innovation after crossing the municipal margins [32]. Wang and Wu suggested that foreign investment can enhance the competitiveness among local enterprises, promote the output of innovative achievements, and thus improve regional innovation capacity [33].…”
Section: The Influence Of High-tech Industry Agglomeration On Regiona...mentioning
confidence: 99%